Gene expression and infectivity of Borrelia afzelii in the course of tick feeding - Pospíšilová, Tereza (Jihočeská univerzita, 2018)
Borrelia afzelii differential gene expression in the course of tick blood-feeding, and during chronic infection in mice was studied. Temperature effect on B. afzelii gene expression and infectivity was investigated. Infection rates of mice immunized with B. afzelii tick gut antigen at various stages of tick blood-intake were analyzed. This work was funded by the Grant Agency of the Czech Republic, Project No. 17-27393S to Radek Šíma.
Gene expression and infectivity of Borrelia afzelii in the course of tick feeding
Keywords: Borrelia; Borrelia afzelii; Lyme disease; Borreliosis; Ixodes ricinus; tick; Lyme disease transmission; Borrelia; Borrelia afzelii; Lyme disease; Borreliosis; Ixodes ricinus; tick; Lyme disease transmission